2018
DOI: 10.1038/s41598-018-28663-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycosphingolipid synthesis reverses skin inflammation and hair loss in ApoE−/− mice fed western diet

Abstract: Sphingolipids have been accorded numerous biological functions however, the effects of feeding a western diet (diet rich in cholesterol and fat) on skin phenotypes, and color is not known. Here, we observed that chronic high-fat and high-cholesterol diet intake in a mouse model of atherosclerosis (ApoE−/−) decreases the level of ceramides and glucosylceramide. At the expense of increased levels of lactosylceramide due to an increase in the expression of lactosylceramide synthase (GalT-V). This is accompanied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“… 29 38 Conversely, treatment with an inhibitor of β-1,4 GalT-V not only decreased the activity of β-1,4 GalT-V and mass of LacCer but also oxidised PC level in a dose-dependent and time-dependent manner, 29 and reversal of skin arterial stiffness and skin phenotype. 38 Previously, we have shown that in cultured human arterial smooth muscle cells and endothelial cells, oxidised PC and TNF-α can dose and time dependently increase the activity of β-1,4 GalT-V, generating LacCer and increasing superoxide generation to induce the expression of cell adhesion molecules, ICAM-1 and PECAM-1. 13 39 Collectively, we hypothesise that β-1,4 GalT-V activation would be expected to exacerbate inflammation via LacCer signalling, especially considering the finding in this study that β-1,4 GalT-V level is significantly elevated in patients with SLE, relative to healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“… 29 38 Conversely, treatment with an inhibitor of β-1,4 GalT-V not only decreased the activity of β-1,4 GalT-V and mass of LacCer but also oxidised PC level in a dose-dependent and time-dependent manner, 29 and reversal of skin arterial stiffness and skin phenotype. 38 Previously, we have shown that in cultured human arterial smooth muscle cells and endothelial cells, oxidised PC and TNF-α can dose and time dependently increase the activity of β-1,4 GalT-V, generating LacCer and increasing superoxide generation to induce the expression of cell adhesion molecules, ICAM-1 and PECAM-1. 13 39 Collectively, we hypothesise that β-1,4 GalT-V activation would be expected to exacerbate inflammation via LacCer signalling, especially considering the finding in this study that β-1,4 GalT-V level is significantly elevated in patients with SLE, relative to healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…A significant increase in sphingolipid metabolism in the AA group was also found compared to that in healthy subjects. Numerous biological functions are attributed to sphingolipids (Chatterjee and Pandey, 2008) and recently, a role for sphingolipid metabolism in hair growth via inflammation was reported (Bedja et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While human aging is accompanied with greying of hair and balding in the vast majority of the global population, these phenotypes are accelerated upon the intake of a western diet and accompanied with several hematosed skin lesions. Interestingly, ApoE −/− mice fed a western diet display a similar pattern of hair loss and hair greying to that in man [ 102 ]. The ApoE protein serves as a ligand for receptors that transport and clear cholesterol.…”
Section: Laccer-centric Pathways Leading To Inflammationmentioning
confidence: 99%
“…On a regular chow diet, ApoE −/− mice grow lush black hair. However, chronic feeding of a western diet rich in fat and cholesterol for 8 weeks (from 12 weeks of age to 20 weeks) results in greying of hair and patches of hairless skin [ 102 ], resembling patients with decreased hair production also known as alopecia. Upon continuation of feeding western diet up to the age of 36 weeks, nearly 80% of the mouse body becomes devoid of hair and several hemotosed skin patches appear [ 102 ].…”
Section: Laccer-centric Pathways Leading To Inflammationmentioning
confidence: 99%
See 1 more Smart Citation